Efectividad de los ejercicios propioceptivos y fortalecimiento muscular en adolescentes con esguince de tobillo grado 2 que acuden a la Federación Deportiva de “Los Ríos” junio-septiembre 2024. - Campbell Chávez, Jean Paul (2024)
The present investigation was carried out with the objective of determining the effectiveness of proprioceptive exercises and muscle strengthening in adolescents with a grade II ankle sprain who attend the “Los Ríos” Sports Federation June-September 2024. The methodology of the study is mixed (qualitative -quantitative), with a type of applied research, using the deductive method based on three types of study: bibliographic, cross-field and pre-experimental. The information was collected using direct observation techniques, physiotherapy evaluation, pre- and post-intervention measurements, as well as a satisfaction survey based on a sample made up of 30 athletes who attend the FEDERIOS rehabilitation center, who coincided with the inclusion criteria and established exclusion. The Microsoft Excel computer program is used for data processing and analysis. The exercise plan proved to be beneficial in reducing pain, since 60% of athletes described it as mild in intensity after completing the treatment. A significant increase in inversion and flexion muscle strength was shown, simultaneously with improvements in ankle stability and in balance tests, increases in displacement distance were recorded, in all directions (anterior, lateral and posterior). These data mean the great result that was achieved with the training, in short, the training applied was effective in improving the functionality of the athletes, highlighting the importance of proprioception and muscle strengthening in the rehabilitation of grade II ankle sprains.